Diversification in Context: a Cross National and Cross Temporal Extension - Whittington, R; Mayer, M (2003)
This research note examines the stability of diversification performance relationships in three countries (France, Germany and the United Kingdom), for two time periods (1982–84 and 1992–94). The aggregate findings, taking the three countries and two time periods together, support a general model favoring related-constrained diversification. However, disaggregated analyses show sharp variations in different countries and time periods. The note concludes that although broad performance relationships can be found, these can be expressed very differently in particular contexts. We consider implications for further research.